Monitoring of PV Inverters while Unintentional Islanding Using PMU - Szymon Henryk Barczentewicz; Tomasz Lerch; Andrzej Bień (International Journal of Electronics and Telecommunications, 2021)
Unintentional islanding detection is one the mandatory criterion that must be met by PV inverters before connecting them into the grid. Acceptable time for inverter for islanding detection is less than 2 seconds. In this paper voltage parameters after islanding occurrence and before turning off the inverter are analyzed. In order to simulate islanding state and perform measurements the testing system was build. Three different commercial PV inverters were tested. Measured signals were used to calculate voltage envelope, phasor, frequency and ROCOF. Collected data proved to be helpful to compere different inverters.